Lasius Xerophilus (Hymenoptera: Formicidae), a New Ant Species From White Sands National Monument, New Mexico - William P. Mackay; Emma E. Mackay (Psyche: A Journal of Entomology)
We describe a new species of the ant genus Lasius collected from the arid Chihuahuan Desert, a very unusual habitat for the genus. The workers, females and males of this species are similar to those of L. neoniger , but have more abundant erect hairs on the tibiae.